2023
DOI: 10.3390/en16041895
|View full text |Cite
|
Sign up to set email alerts
|

Regenerative Braking Algorithm for Parallel Hydraulic Hybrid Vehicles Based on Fuzzy Q-Learning

Abstract: The use of regenerative braking systems is an important approach for improving the travel mileage of electric vehicles, and the use of an auxiliary hydraulic braking energy recovery system can improve the efficiency of the braking energy recovery process. In this paper, we present an algorithm for optimizing the energy recovery efficiency of a hydraulic regenerative braking system (HRBS) based on fuzzy Q-Learning (FQL). First, we built a test bench, which was used to verify the accuracy of the hydraulic regene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…In order to compare the energy saving efficiency of regenerative braking mor prehensively, 21 previous studies on regenerative braking are listed in In order to compare the energy saving efficiency of regenerative braking more comprehensively, 21 previous studies on regenerative braking are listed in [27] electric vehicles fuzzy Q-learning UDDS 8.91% Zhao et al [28] hybrid electric vehicles fuzzy optimization NEDC 1.22% Li et al [70] electric vehicles fuzzy control method NEDC 9.12% Wu et al [92] dual-motor EVs genetic algorithm self-defined braking 22.8% Yin et al [93] hybrid electric vehicles Q-learning network self-defined braking 7.4% Zhang et al [106] designed a Sugeno fuzzy logic controller which has three inputs, the driver's braking requirements, vehicle speed, and battery SOC, and one output, regenerative braking force. They indicate that in the UDDS drive cycle, the energy saving efficiency reaches 22.29%.…”
Section: Performance Of Regenerative Brakingmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to compare the energy saving efficiency of regenerative braking mor prehensively, 21 previous studies on regenerative braking are listed in In order to compare the energy saving efficiency of regenerative braking more comprehensively, 21 previous studies on regenerative braking are listed in [27] electric vehicles fuzzy Q-learning UDDS 8.91% Zhao et al [28] hybrid electric vehicles fuzzy optimization NEDC 1.22% Li et al [70] electric vehicles fuzzy control method NEDC 9.12% Wu et al [92] dual-motor EVs genetic algorithm self-defined braking 22.8% Yin et al [93] hybrid electric vehicles Q-learning network self-defined braking 7.4% Zhang et al [106] designed a Sugeno fuzzy logic controller which has three inputs, the driver's braking requirements, vehicle speed, and battery SOC, and one output, regenerative braking force. They indicate that in the UDDS drive cycle, the energy saving efficiency reaches 22.29%.…”
Section: Performance Of Regenerative Brakingmentioning
confidence: 99%
“…A dual-layer, multi-parameter regenerative braking control technique was put forward by Geng et al [26], and it was shown to considerably increase the ability of vehicles to recover energy. A fuzzy control technique was developed by Ning et al [27] with a 5.4% increase in the effective recovery rate of regenerative braking energy. Fuzzy optimization algorithms were utilized by Zhao et al [28] to reduce battery usage by 1.22%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Geng et al [26] proposed a dual-layer multi parameter control strategy for braking energy recovery, which significantly improves the energy recovery efficiency of the vehicle. Ning et al [27] proposed an energy recovery efficiency optimization algorithm based on fuzzy Q-learning. Under the conditions of the UDDS cycle, the energy recovery efficiency was improved by approximately 9%.…”
Section: Introductionmentioning
confidence: 99%